Advanced field shimming technology to reduce the influence of a screening current in a REBCO coil for a high-resolution NMR magnet. (11th March 2016) - Iguchi, S; Piao, R; Hamada, M; Matsumoto, S; Suematsu, H; Takao, T; Saito, A T; Li, J; Nakagome, H; Jin, X; Takahashi, M; Maeda, H; et al.
Abstract: This paper describes a field shimming technology to obtain a spatially homogeneous magnetic field required for a high-resolution nuclear magnetic resonance (NMR) magnet under the influence of a screening current in a (RE)Ba2 Cu3 O7– x (REBCO) coil. Use of REBCO inner coils is one solution to realize a super-high field (>23.5 T, 1 GHz) NMR magnet. However, a REBCO coil generates a large amount of field error harmonics due to the inhomogeneous coil winding introduced by a thin tape conductor. In addition, the performance of a field correction coil and outer superconducting (SC) shim coils are significantly reduced due to the shielding effect of the screening current in the REBCO coil. Therefore, conventional shimming technology using SC shim coils and room temperature shim coils cannot adequately compensate those field error harmonics and high-resolution NMR measurements are not possible. In the present paper, an advanced field shimming technology including an inner SC shim coil and a novel type of ferromagnetic shim were installed in a 400 MHz low-temperature SC/REBCO NMR magnet. The inner SC shim coil and the ferromagnetic shim compensated for the reduction in the performances of the field correction coil and the SC shim coils, respectively. The field error harmonics were greatly compensated with the technology and a high NMR resolution <0.01 ppm was obtained. The results from the present work suggest an optimal shimming procedure for a super-high field NMR magnet with high-temperature superconductors inner coils, i.e. the best mix of shims.